The Importance Of Character Education In Instilling Pancasila Values For Millennial Generation - Tri Budi Haryoko; Encep Syarief Nurdin; Yadi Ruyadi; Tri Suhartati (Eduvest - Journal of Universal Studies, 2024)
Millennial generation as a new generation that emerges as a pioneer of information technology development in the era of 4.0. They are called the millennial generation because they were born at the end of the 20th century (between 1990 and 2001). The millennial generation, living in the millennium era, is heavily influenced by lifestyles shaped by social media as a societal trend in the 21st century. Many potential social vulnerabilities will arise due to cultural and behavioral changes that occur in the millennium era. The widespread use of smartphones, internet access, and social media today enables quick and easy access to information, which has its benefits and advantages, but also impacts by facilitating access to negative content that affects behavior not in line with the culture and noble norms of the Indonesian nation. Character education, as a model of education that strengthens the understanding of Pancasila ideology, is essential in fortifying and equipping the millennial generation. With systematically implemented character education, it is hoped to maintain attitudes and behaviors so that they always preserve the customs, cultural heritage, and noble values of the Indonesian nation in facing the massive technological developments in the current millennium era.